Aerial Photo Quality on various altitude - Putra, I Wayan Aris Santika; Wijaya, I Made Anom S.; Gunadnya, I.B. Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The aim of this research is to find aerial photoraphy acquisition altitude with the best quality image The acquisition of aerial photography done by drones. Altitude of aerial photography acquisition were 10m, 20m and 30m. aerial photos taken a image of ciherang rice varieties with the age of 100 days after planting. Detailed analysis of aerial photography was done by zooming and image binary. Zooming process was used Adobe Photoshop CS6 software. binary imagery process was used MatLab Software 2013 software. 10m acquisition altitudehas the best quality of detail.